2008
DOI: 10.1111/j.1600-0706.2008.16722.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the relative importance of patch quality and connectivity in a damselfly metapopulation from a one‐season survey

Abstract: The area‐and‐isolation paradigm, which has been the primary focus of metapopulation research, may not hold in some animal metapopulations if within‐patch preference is more important than patch area or connectivity. Recently, regression analyses have been used to evaluate the effect of patch connectivity and various patch qualities including area. However, their relative importance is not easy to determine, because patch qualities and connectivity are often spatially autocorrelated. In this paper, we try to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 56 publications
0
30
1
Order By: Relevance
“…Previous research characterizing the independent or interactive influences of patch quality indicated that this variable can exert significant effects on local population performance, with some studies demonstrating that local habitat quality can have the highest independent effect on local population dynamics (Betzholtz, Ehrig, Lindeborg, & Dinnétz, 2007;Jaquiery et al, 2008;Mortelliti et al, 2010;Pöyry, Paukkunen, Heliölä, & Kuussaari, 2009;Root, 1998;Yamanaka et al, 2009). Similarly, across the patch attribute gradients present in this study, the independent effects of patch quality had a greater influence on the risk of regional extinction than the common indices of patch size and proximity.…”
Section: Patch-levelmentioning
confidence: 51%
“…Previous research characterizing the independent or interactive influences of patch quality indicated that this variable can exert significant effects on local population performance, with some studies demonstrating that local habitat quality can have the highest independent effect on local population dynamics (Betzholtz, Ehrig, Lindeborg, & Dinnétz, 2007;Jaquiery et al, 2008;Mortelliti et al, 2010;Pöyry, Paukkunen, Heliölä, & Kuussaari, 2009;Root, 1998;Yamanaka et al, 2009). Similarly, across the patch attribute gradients present in this study, the independent effects of patch quality had a greater influence on the risk of regional extinction than the common indices of patch size and proximity.…”
Section: Patch-levelmentioning
confidence: 51%
“…Exact test of population differentiation showed significant difference (P \ 0.05) among three C. tokyoensis populations that are closely located (\20 km). For the dispersal ability of C. annulata, Yamanaka et al (2009) estimated the generational mean dispersal distance to be 53 m. This very short dispersal behavior connects neighboring patches and the patches make clusters at the scale of the medium spatial category (640 m; Yamanaka et al 2009). If these two Copera species shows similar tendency of small range dispersion, the genetic differentiation of C. tokyoensis might be explained by the low-dispersal ability of females.…”
Section: Genetic Diversity and Population Differentiationmentioning
confidence: 99%
“…The colonization of odonates in isolated habitat patches is limited by the dispersal capability and behavior of each species 1,8,15 . It is also limited by the differences in landscape structure among the habitats 16,28,41 . The effect of the differences in connectivity and landscape structure among ponds on regional odonate populations is an important area of future research.…”
Section: Conservation Considerationsmentioning
confidence: 99%
“…Previous field studies on factors affecting odonate species have identified the importance of aquatic and riparian vegetation 7,31 , predatory fish 21,22,25,27 , water quality 3,4 , landscape structure 16,20,29,41 , and spatial autocorrelation 15 . However, these studies have investigated either a single or several environmental factors.…”
Section: Introductionmentioning
confidence: 99%